Concept development of a cooling system for electronic speed controller’s onboard hydro-foiling vessels - Grenestedt, Carl-Johan; Winbo, Carl Johan (My University, 2023)
This bachelor thesis is written as a final part of the studies at Chalmers University of Technology in the marine engineering program. The work has been conducted on behalf of the Swedish Sea Rescue Society and in collaboration with SIGMA Energy and Marine. The Swedish Sea Rescue Society has developed a new rescue boat with hydrofoil construction and an electric drivetrain through a cooperative project, with assistance from several companies. The reason for the hydrofoil design is to reduce resistance between the hull and the water, which leads to lower energy consumption and increased range. Electronic speed controllers are used to control the speed of the electric motors and in this application the speed of the boat. When the speed controllers are in operation, energy is consumed, resulting in heat generation in the electronic speed controllers. SSRS wants to ensure the reliable function of their vessel and that no critical temperatures are reached. A cooling system that conducts heat away from the electronic speed controllers is required to accomplish this. The problem with high temperatures is that it reduces efficiency, reduces performance, and shorten the life of the controllers. In the end, critical temperatures will cause the controllers to shut down. The work aims to develop a cooling system for speed controllers that can be implemented onboard SSRS’s rescue boat which is of hydrofoil construction. The development of cooling systems is based on the needs of the sea rescue and designed according to their ship structure. This report does not include the development of a whole cooling system with external components.
Keywords: Hydrofoil; Ship; Vessel; Boat; Electronic speed controllers; Cooling systems; Heat exchanges